PENGARUH PENGETAHUAN KEPALA SEKOLAH TENTANG ROKOK DAN KAWASAN TANPA ROKOK TERHADAP DUKUNGAN PENERAPAN WILAYAH KAWASAN TANPA ROKOK DI SEKOLAH SD, SLTP DAN SLTA DI KOTA LANGSA TAHUN 2012 - khairul fuad; Juanita siregar; Rusmalawaty harahap (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
ABSTRACT The no smoking area is a space that prohibited for any production, selling, advertisement and promotion and smoking activities. The no smoking area is a protection to the public on the health threat risk. The teaching learning process area is one of location without smoking. Langsa city has not yet implement the no smoking area especially in teaching learning process area as determined in Act No. 36 of 2009 regarding the health. This research was an explanatory research that aims to describe the influence of the knowledge to the principal or headmaster about the smoking and no smoking area in order to support the no smoking area in SD, SLTP and SLTA in Langsa of 2012. The population was all of Principals of SD, SLTP and SLTA of 122 schools and the sample was took by simple random sampling by the number of sample was 55 principals. The applied statistical test was multi regression logistic. The results of bivariate statistical test indicates that both of variables has influence to the support of implementation of no smoking area i.e. knowledge of principal about cigarette (p=0.000) and the knowledge of principal about the no smoking area (p=0.000). The results of multivariate statistical test in which the two variables together, knowledge about smoking variables exert significant influence because the value of p (= 0.037), knowledge of the variable region without a cigarette does not give effect to support the implementation of the no-smoking areas, namely p = (0.704). In order to realized the no smoking area it requires a solid cooperation of any parties, the self awareness and readiness in provide the support without any force and has accountability in realize the no smoking area.